Regional-scale compositional and size fidelity of rocky interdidal comminities from the patagonian atlantic coast - Archuby, Fernando M. (2015)
Fil: Archuby, Fernando M.. Instituto de Investigación en Paleobiología y Geología. Universidad Nacional de Río Negro. General Roca; Argentina